Sequence variation and structural conservation allows development of novel function and immune evasion in parasite surface protein families. (19th February 2014) - Higgins, Matthew K.; Carrington, Mark
Abstract Trypanosoma and Plasmodium species are unicellular, eukaryotic pathogens that have evolved the capacity to survive and proliferate within a human host, causing sleeping sickness and malaria, respectively. They have very different survival strategies. African trypanosomes divide in blood and extracellular spaces, whereas Plasmodium species invade and proliferate within host cells. Interaction with host macromolecules is central to establishment and maintenance of an infection by both parasites. Proteins that mediate these interactions are under selection pressure to bind host ligands without compromising immune avoidance strategies. In both parasites, the expansion of genes encoding a small number of protein folds has established large protein families. This has permitted both diversification to form novel ligand binding sites and variation in sequence that contributes to avoidance of immune recognition. In this review we consider two such parasite surface protein families, one from each species. In each case, known structures demonstrate how extensive sequence variation around a conserved molecular architecture provides an adaptable protein scaffold that the parasites can mobilise to mediate interactions with their hosts.